Academic Integrity in Higher Education: Analysis of Research Publication and Web Citation - Abdullah, Aziman; Abdul Karim, Asar (KnE Social Sciences, 2019)
Higher education is a critical organization for nation-building, either for economic development or social well-being. However, this noble and vital institution has been affected by the issue of “academic integrity” due to digital technology adoption, the Internet. Many research studies have been conducted and published, but the impact on the institution and society yet not been properly reported. This study attempts to assess the impact of research on academic integrity by exploring its relationship with web citation. Quantitative method is adopted by analyzing data collected from Google Scholar, SCOPUS, and aHref web analytics cloud service. A strong positive correlation (Pearson’s coefficient = 0.915) of the published research works on “academic integrity” with web citation can be used as an effective strategy to put research into action in academic integrity. Thus, this study suggests that web citation is a potential metrics that can be used as an effective tool to measure the impact of research in academic integrity.